Troubling nationhood in U.S. Latina literature : explorations of place and belonging - Socolovsky, Maya, 1973-; American Literatures Initiative (New Brunswick, New Jersey : Rutgers University Press, 2013)
This book examines the ways that U.S. Latina literature challenges popular definitions of nationhood and national identity. It explores the works of Mexican American, Puerto Rican, and Cuban American writers Denise Chavez, Ana Castillo, Sandra Cisneros, Judith Ortiz Cofer, Esmeralda Santiago, and Himilce Novas to show how these texts argue for the legitimate belonging of Latino/as within U.S. borders and counter anti-immigration rhetoric.
Introduction : Troubling America(s) -- Spaces of the Southwest : dis-ease, disease, and healing in Denise Chávez's The last of the menu girls and Face of an angel -- Mestizaje in the Midwest : remapping national identity in the American heartland in Ana Castillo's Sapogonia and Sandra Cisneros' Caramelo -- Colonization and transgression in Puerto Rican spaces : Judith Ortiz Cofer's Line of the sun and The meaning of Consuelo -- Memoirs of resistance : colonialism and transnationalism in Esmeralda Santiago's When I was Puerto Rican, Almost a woman, and The Turkish lover -- Tales of the unexpected : Cuban-American narratives of place and body in Himilce Novas' Princess papaya -- Postscript : The illegal aliens of American letters : troubling the immigration debate.
Includes bibliographical references (pages [195]-237) and index.
Print version record.
JSTOR
Keywords: American literature -- Hispanic American authors -- History and criticism; American literature -- Women authors -- History and criticism; Hispanic American women -- Intellectual life; Hispanic Americans in literature; Belonging (Social psychology); Identity (Psychology) in literature; National characteristics, Latin American, in literature; Littérature américaine -- Auteurs américains d'origine latino-américaine -- Histoire et critique; Écrits de femmes américains -- Histoire et critique; Américaines d'origine latino-américaine -- Vie intellectuelle; Américains d'origine latino-américaine dans la littérature.; Appartenance (Psychologie sociale); Identité (Psychologie) dans la littérature.; LITERARY CRITICISM -- American -- General; LITERARY CRITICISM -- American -- Hispanic American; American literature -- Hispanic American authors; American literature -- Women authors; Belonging (Social psychology); Hispanic American women -- Intellectual life; Hispanic Americans in literature; Identity (Psychology) in literature; National characteristics, Latin American, in literature; Criticism, interpretation, etc